Hyperloop Locomotive - Amri A. N,; Shamri S. N. I,; Nasir S. N.,; Asril Rajo Mantari, Muhammad Hanafi (Multidisciplinary Applied Research and Innovation, 2023)
Hyperloop is a magnetic transfer and lifting concept that allows locomotives to move at higher speeds than the conventional train. This hyperloop also uses tubes for regular power trains. In hyperloop systems, this is referred to as EMF or Electromotive Force. EMF is a type of electrical activity produced by a non-electrical source or a device that converts other energy sources into electrical energy, such as a battery or generator. EMF operates on three principles: electromagnetic suspension (EMS), electrodynamic suspension (EDS), and inductrack. This project seeks to provide learning tools and introduction sessions linked to the principles employed in the hyperloop. The method used to create this hyperloop train uses 18650 lithium-ion batteries, neodymium magnets and a 3D printer with filament. The results show that the hyperloop runs smoothly and quickly through various processes. The first is battery power affecting the speed process with a high charge of 4.65 cm/s, two magnets on each side with a velocity of 4.65 cm/s. Up next, lithium-ion batteries in blue have reliable electric power, and the last light load accelerates the train's movement with a speed of 4.08 cm/s. Meanwhile, the suggested hyperloop idea has been designed for proof-of-concept testing to evaluate its functionality and capabilities. Several actions have been discussed; in summary, the hyperloop locomotive has been successfully constructed and validated through proof-of-concept testing.